Students’ Perceptions of Women in Policing: The Role of Media Portrayal and Representation of Policewomen - Asare Yeboah, Alberta Mayfair (International Journal of Criminology and Sociology, 2025)
Purpose: Diversity and representation are important for organizational growth and sustainability, particularly in policing, where women are highly underrepresented. Although attitudinal research in policing is extensive, little has been done to assess factors that influence citizens’ perceptions of women in policing. This study, therefore, investigates the effects of media and film representation of women in policing on students’ perceptions of the female police officer. Design/Methodology: Using a cross-sectional design, the study obtained data from 152 university students enrolled in one of the major research institutions in a southern state of the U.S. during the 2023-2024 academic year. Findings: Using a multivariate analytical approach, the study did not support the hypothesis that negative portrayals of policewomen in media significantly influence students’ perceptions. Originality: The findings of the study provide information that could be useful for improving citizens’ attitudes toward women in policing and enhancing the police-citizens relationship. The manuscript offers an original contribution to the study of policing, especially as it relates to factors that influence perceptions of police officers.